Theoretical-Methodological Aspects of Integrated Risk Management Standardization - Milan Majernik; Jana Pankova Jurikova (Communications - Scientific letters of the University of Zilina, 2011)
The authors are submitting a system model for integrated risk management. Results and conclusions of the paper are based on analysis of development, current status and progressive trends in standardization and risk management aspects of quality, safety, environment etc. Originality of the solution lies “in an enclosure” of quality management systems, safety management system and environmental management system according to standards, under the ISO standard ISO 31000 in the Slovak version of the upcoming STN. Solution is based on the philosophy of a single audit of compliance for the accreditation of certification bodies – they will certify risk management system. First audit can be realized for the certification system and the second for implementation system. The prepared standard ISO 31000 would be certification’s standard.